Hammond, M. 2006. Phonological Universals. In K. Brown (ed.), Encyclopedia of Language and Linguistics. Oxford: Elsevier: 525-531. - Silva, Carlos S. (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
.